2019
DOI: 10.1055/s-0039-3399476
|View full text |Cite
|
Sign up to set email alerts
|

Access to the Intensive Care Unit by Severe Head Injury Patients

Abstract: Background The management of severe traumatic brain injury is directed at avoidance of secondary brain injuries. The intensive care unit (ICU) provides the ideal environment to achieving improved survival and functional outcome. The study sets out to identify the factors that determine the access of patients with severe head injury presenting at our hospital, to the ICU and their impact on outcome. Materials and Methods his was a longitudinal study at the University College Hospital, Ibadan. Data of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Severely injured patients require intensive care for many reasons. [ 2 ] This study showed that about 40% of trauma victims had blood pressure in the hypotensive range (systolic blood pressure <90 mmHg). However, in the article, we could not trace any mention about intensive care unit (ICU) admission and ICU related mortality.…”
mentioning
confidence: 99%
“…Severely injured patients require intensive care for many reasons. [ 2 ] This study showed that about 40% of trauma victims had blood pressure in the hypotensive range (systolic blood pressure <90 mmHg). However, in the article, we could not trace any mention about intensive care unit (ICU) admission and ICU related mortality.…”
mentioning
confidence: 99%